MAKNA VERBA 流れる‘NAGARERU’ SEBAGAI POLISEMI DALAM KALIMAT BAHASA JEPANG (KAJIAN SEMANTIK) - Tiara Diahtantri Riannisa; Silvia Lestin; Nunik Nur Rahmi Fauzah (Universitas Negeri Jakarta, 2025)
In Japanese there are verbs that have multiple meanings or are called polysemy (tagigo). This study aims to describe the basic meaning and extended meaning of nagareru verbs, as well as the relationship between its meaning as a polysemy in Japanese sentences. The research data comes from the ninjal corpus. The research method used is a descriptive qualitative method. The data collection was done by listening and note-taking techniques. In this study, the data were analyzed based on the theory of basic meaning and expansion meaning of nagareru verbs from kokugo.jitenon.jp online dictionary. The author has found 46 data with 10 data of basic meaning, and 36 data of expansion meaning. The analysis found that nagareru verbs have four basic meaning categories and ten extended meanings. The basic meaning categories of nagareru verbs are moving liquids, moving objects following the movement of liquids, movement of objects by wind and liquids coming out of the body. The expanded meanings are exile or banishment, something spreading, change of time, blood relationship or lineage, annulment, wandering aimlessly, tending towards bad, loss of ownership, miscarriage, and illegal sale. However, the use of the verb nagareru with the meaning of ‘miscarriage’ is difficult to find.